FRI0012 Sharing the burden of rheumatoid arthritis through remote monitoring of rheumatoid arthritis (REMORA): implications for patients and clinicians. (12th June 2018) - Sharp, C.A.; Austin, L.; Machin, M.; Humphreys, J.; Mellor, P.; McCarthy, J.; van der Veer, S.; Davies, L.; Ainsworth, J.; Sanders, C.; Dixon, W.
Abstract : Background: People living with rheumatoid arthritis (RA) experience continuous, daily symptoms that fluctuate over time. Clinical decisions made by healthcare professionals at intermittent consultations rely upon history taking, which is subject to pitfalls including recall bias, variable help-seeking behaviours and difficulty in summarising fluctuating symptoms. Objectives: REmote MOnitoring in Rheumatoid Arthritis (REMORA) was a pilot study to design, implement and evaluate a system of remote data collection for RA patients, for health and research purposes. A unique feature was its aim to integrate patient-generated data from a smartphone app into the electronic health record (EHR). Methods: Semi-structured interviews with key stakeholders informed project design and evaluation, comprising three stages: 1) co-design of smartphone app prototype and integration into the electronic patient record (EHR); 2) end-to-end prototype testing (1 month); 3) evaluation of feasibility and acceptability (3 months). Qualitative data from audio-recorded interviews and 'routine' consultations, following app use, were coded using a priori and emergent themes, and triangulated. Results: Daily, weekly and monthly question sets were developed. Patients tracked daily symptoms for one month (n=8) and three months (n=20). Patients submitted daily scores on most days (median 91% of days; IQR 78%>95%) with 4/20 patients submitting on <60% days. Further detail on feasibility has been reported elsewhere. 1 REMORA data were successfully integrated into the EHR (figure 1). Data from interviews with 16 patients, 2 clinician-researchers (WD and CAS) and 17 clinical consultations were analysed. Patients and clinicians found remote monitoring acceptable and easy to use. Three themes emerged with REMORA data providing the 'bigger picture' by highlighting episodes that might otherwise have been missed, for example short-lived flares and gradual changes in disease; empowering patients through increased self-awareness and improved understanding of RA; and changing the nature of consultations with graphs integrated into the EHR facilitating shared conversations and leading to more personalised care. Conclusions: This study demonstrates the acceptability and feasibility of the REMORA system. Novel integration of patient-generated data into the EHR positively impacted consultations and was felt to empower patients. The system generated a unique, temporally-rich research dataset. The next challenge is to scale-up and spread the adoption of this innovation across a range of clinical contexts. Reference: [1] Van Der Veer S, Austin L, Sanders C, Dixon W. FRI0175 Using smartphones to improve remote monitoring of rheumatoid arthritis: completeness of patients' symptom reports. BMJ Publishing Group Ltd2017. Disclosure of Interest: None declared